Impact of Preoperative Neuropraxia on Surgical Duration Following Pediatric Supracondylar Fracture of the Humerus: A Retrospective Cohort Study - Alayed, Yazeed; Alrashedan, Bander S.; Almisfer, Sultan K.; Aldossari, Ali M. (Journal of Brachial Plexus and Peripheral Nerve Injury, 2023)
Background Supracondylar fractures of the humerus (SCFHs) are the most common type of elbow fracture in children. Because of the influence on functional outcome, neuropraxia is one of the most common concerns at presentation. The impact of preoperative neuropraxia on surgery duration is not extensively probed. The clinical implications of several other risk factors associated with preoperative neuropraxia at presentation may contribute to longer surgical duration of SCFH.Hypothesis Preoperative neuropraxia is likely to increase surgery duration in patients who sustained SCFH.Patients and Methods This is a retrospective cohort analysis. Sixty-six patients who sustained surgical pediatric supracondylar humerus fracture were included in the study. Baseline characteristics including age, gender, the type of fracture according to Gartland classification, mechanism of injury, patient weight, side of injury, and associated nerve injury were included in the study. Logistic regression analysis was performed using mean surgery duration as the main dependent variable and age, gender, fracture type according to the mechanism of injury, Gartland classification, injured arm, vascular status, time from presentation to surgery, weight, type of surgery, medial K-wire use, and afterhours surgery as the independent variables. A follow-up of 1 year was implemented.Result The overall preoperative neuropraxia rate was 9.1%. The mean surgery duration was 57.6 ± 5.6 minutes. The mean duration of closed reduction and percutaneous pinning surgeries was 48.5 ± 5.3 minutes, whereas the mean duration of open reduction and internal fixation (ORIF) surgeries was 129.3 ± 15.1 minutes. Preoperative neuropraxia was associated with an overall increase in the surgery duration (p < 0.017). Bivariate binary regression analysis showed a significant correlation between the increase of surgery duration and flexion-type fracture (odds ratio = 11, p < 0.038) as well as ORIF (odds ratio = 26.2, p < 0.001).Conclusion Preoperative neuropraxia and flexion-type fractures convey a potential longer surgical duration in pediatric supracondylar fracture.Level of Evidence Prognostic III.
Keywords: child; supracondylar humeral fractures; recovery of function; prognosis; K-wires